PENGUJIAN KONSUMSI BAHAN BAKAR PADA ENGINE TRAINER CARRY ST 100 - , GRYMMALDI HARINDAH; , Ir.Susanto Johanes, MT. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Today, the automotive world has been rapidly development. This is supported by the progress engine system which has electronic device, especially in terms of improving the efficiency of a fuel. The efficiency of fuel in a vehicle is affected by the system, so that the complete combustion of fuel and air to be burned in accordance with the specifications of the vehicle. In addition, it will be more efficient. This is beneficial to the people. This practical work is aimed to learn and explore further the efficiency of a fuel with testing fuel consumption of the Suzuki carry ST 100 engine trainer. In testing fuel consumption by using Suzuki carry ST 100 engine trainer which has a capacity of 1000 cc, used 4 stroke type